2005
DOI: 10.1002/lt.20338
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with methicillin-resistantStaphylococcus aureusafter liver transplantation

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a frequent cause of infection after orthotopic liver transplantation (OLT). Colonization with MRSA is associated with a higher risk of infection. Previous studies have shown a high prevalence of MRSA colonization among OLT candidates. However, the risk of colonization with MRSA after OLT is still unclear. The objective of this study was to estimate the incidence and the factors associated with colonization with MRSA after OLT. This was a prospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
2
17
1
Order By: Relevance
“…The 6.7% probability of detecting MRSA by ASC was lower than that of some recent ICU-based studies, potentially reflecting differences in the frequency of performing ASC and the impact of control measures on decreasing the risk of MRSA acquisition in the study ICU. Santoro-Lopes and colleagues reported an MRSA colonization rate of 15% among liver transplant recipients over a 72-day study period during which five nasal swab specimens were collected (18). This prevalence rate was similar to the cumulative prevalence of MRSA that we detected by ASC (11.1%) performed only on admission over a substantially longer follow-up period.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The 6.7% probability of detecting MRSA by ASC was lower than that of some recent ICU-based studies, potentially reflecting differences in the frequency of performing ASC and the impact of control measures on decreasing the risk of MRSA acquisition in the study ICU. Santoro-Lopes and colleagues reported an MRSA colonization rate of 15% among liver transplant recipients over a 72-day study period during which five nasal swab specimens were collected (18). This prevalence rate was similar to the cumulative prevalence of MRSA that we detected by ASC (11.1%) performed only on admission over a substantially longer follow-up period.…”
Section: Discussionsupporting
confidence: 78%
“…Liver transplant candidates and recipients are at increased risk of colonization with multidrug-resistant organisms, including MRSA and VRE, because of critical illness, prolonged hospitalization and broad-spectrum antimicrobial use, organ dysfunction, invasive devices and procedures and immune suppression (3,7,14). However, studies that have examined the clinical impact of MRSA and VRE colonization among liver transplant candidates and recipients may be limited by failure to adjust for severity of illness or other confounders, limited study duration and small sample size (9,(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…MRSA infection after DDLT has been well described in previous reports (5, 6, 8–11); however, LDLT is different from DDLT in some respects. First, in LDLT, small‐for‐size grafts (13) are often transplanted in adults because the available liver volume from the living donor is limited.…”
mentioning
confidence: 71%
“…In some centers, 91% (45 of 49 isolates) of all S. aureus infections after DDLT were caused by MRSA (7). Long‐term use of a urinary catheter, postoperative bleeding at the surgical site, and preoperative use of fluoroquinolones independently increased the risk of MRSA colonization after liver transplantation (11). The clinical outcome of MRSA infection differs from that of MRSA colonization (12) however, and therefore MRSA infection after liver transplantation also should be studied.…”
mentioning
confidence: 99%
“…The frequent wound and urinary tract infections of this phase are increasingly being caused by antibiotic‐resistant strains (vancomycin‐resistant enterococci and methicillin‐resistant Staphylococcus aureus , MRSA) [3, 4]. In a recently published study on 60 liver transplant recipients, 15% demonstrated MRSA on nasal swabs for the first time during inpatient treatment [5].…”
Section: Dermatologic Infections Following Organ Transplantationmentioning
confidence: 99%